2019
DOI: 10.1177/2309499019854039
|View full text |Cite
|
Sign up to set email alerts
|

Patella alignment abnormality in patients with developmental dysplasia of the hip

Abstract: Background: The purpose of this study was to assess the influence of developmental dysplasia of the hip (DDH) on patella alignment. Methods: The radiographic data of all the patients who met the inclusion criteria from January 2015 to July 2017 were reviewed, including the quadriceps angle (QA), patellar lateral tilt (PTA), sulcus angle (SA), lateral shift of patella (LSP), and lower limbs alignment. The patients were divided into three groups in accordance with lateral center-edge angle (LCE) and femoral neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Researchers, like Hu et al, also confirmed that DDH could lead to abnormal patella alignment and patella instability. 26 Similarly, in our study, we found that patients with recurrent dislocation of patella combined with TD also experienced changes in hip morphology. Therefore, in the process of clinical treatment, besides considering the disease of the knee joint, attention should also be paid to morphological changes of the hip joint, and the hip joint should be evaluated.…”
Section: Discussionsupporting
confidence: 75%
“…Researchers, like Hu et al, also confirmed that DDH could lead to abnormal patella alignment and patella instability. 26 Similarly, in our study, we found that patients with recurrent dislocation of patella combined with TD also experienced changes in hip morphology. Therefore, in the process of clinical treatment, besides considering the disease of the knee joint, attention should also be paid to morphological changes of the hip joint, and the hip joint should be evaluated.…”
Section: Discussionsupporting
confidence: 75%
“…The TT-TG measurement is the distance between lines "b" and "c" line is the perpendicular line from the medial edge of the patella to the tangent line of the posterior condyle. If LSP is greater than 5 mm, it is defined as lateral patella shift [18].…”
Section: Methodsmentioning
confidence: 99%
“…During clinical practice, we noticed that some patients with DDH complained of anterior knee pain (AKP) before and after PAO surgery. Previous studies have reported that patients with hip dysplasia also have knee anatomical deformities [18][19][20]. Therefore, this study intends to analyze the anatomical characteristics of the knee joints of DDH patients and the impact of PAO surgery on the patellofemoral joint (PFJ).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental dysplasia of the hip (DDH) is associated with morphological changes in the knee joint [1][2][3][4]. The femoral condyles of dysplastic hips are smaller and asymmetric, the trochlea is more shallow, the lateral patellar shift is reduced, the patellar tilt angle is increased, and the lower limb alignment is generally in the valgus [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Developmental dysplasia of the hip (DDH) is associated with morphological changes in the knee joint [1][2][3][4]. The femoral condyles of dysplastic hips are smaller and asymmetric, the trochlea is more shallow, the lateral patellar shift is reduced, the patellar tilt angle is increased, and the lower limb alignment is generally in the valgus [1][2][3][4]. These morphological abnormalities tend to show a linear correlation with the degree of hip dislocation [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%